Implemetasi Aplikasi Toko Online Dengan Optimasi Codeigniter Dan Jquery Mobile Pada Erik Phone - Irma Ayuni; Iqbal Ibal; Riyadhul Fajri (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2024)
The Smartphone Sales Information System is a management information system that produces variousinformation that can be useful to support sales activities at Erik Phone. The manifestation of the development ofthis Smartphone Sales Information System is the creation of a website that is able to represent the informationsystem designed as a whole. The resulting smartphone sales website is able to manage and display informationon various types of smartphones on offer along with price lists, smartphone brands, colors, purchase methods,transactions and sales reports. In analyzing and designing this new system, the author used the systemdevelopment method. Meanwhile, to carry out the analysis process, the author uses context diagrams, DFD andERD. This system was created using the PHP, Jquery and Mysql programming languages. From this analysisand design, a new web-based smartphone sales information system was produced which can help Erik Phonecarry out the smartphone promotion and sales process effectively and efficiently